LED광원이 Botrytis cinerea의 균사 생장에 미치는 영향 - 최은규; 김명훈; 백경윤; 최만권; 윤용철; 김현태; Eun-Gyu Choi; Myeong-Hun Kim; Gyeong-Yun Baek; Man-Kwon Choi; Yong-Cheol Yoon; Hyeon-Tae Kim (농업생명과학연구, 2013)
온실 및 식물공장 작물재배에 있어서 LED 광원과 작물생육에 관한 연구들은 활발히 진행 되고 있으나, LED광원과 식물에 병을 일으키는 식물병원균에 대한 연구들은 미흡하다. LED 광원은 이미 시설재배 혹은 식물공장에 설치되어 있으므로 LED광원으로 식물에 발생하는 병원균을 제어할 수 있다면 방제에 필요한 인적, 시간적 비용과 살균제 등과 같이 인체에 유해한 성분들의 사용을 감소시킬 수 있을 것으로 판단하여 LED광원에 대한 Botrytis cinerea의 균사생장을 조사하였다. 식물공장에서는 주로 엽채류를 재배하며 엽채류에는 여러 가지 곰팡이균들에 의한 질병 발병 가능성이 충분히 내재되어 있다. 병원균의 포자는 항상 작물재배지에 존재하고 있기 때문에 LED 광원이 식물병원균의 균사 생장을 억제 할 수 있다면, 식물공장내에서 작물재배에 효과적으로 이용할 수 있을 것으로 판단된다. 식물공장의 광원중 가장 많이 보편화되어 있는 LED 광원을 이용하여 B. cinerea의 균사 생장을 조사한 결과 Blue 광원에서 균사 생장이 억제되는 것을 관찰할 수 있었다. 이러한 결과는 식물공장내 LED의 비율과 광량의 적절하게 조절함으로써 식물병원균의 증식을 억제 할 수 있을 것으로 판단된다. LED light sources and crop growths studies has been actively conducted in the greenhouse and plant factory, but LED light source and plant pathogens interaction researches are insufficient. LED light source is already installed on the greenhouse and plant factory. If the LED light source can be used to control pathogens, it is needed to control costs and reduce the use of harmful ingredients to human body, so Botrytis cinerea hyphal growth was monitoring under the LED light condition. Plant factory cultivated mainly in leafy vegetables and it occurred several fungal disease. This disease can cause outbreaks in the plant factory, and it is difficult to predict. There is always a certain degree of pathogen spores in the plant factory. If LED light source can be inhibit spore germination of plant pathogens in the plant as well as able to inhibit hypha growth, the leafy vegetables is expected to cultivate effectively. LED light source for the hyphal growth of B. cinerea was observed hyphal growth inhibition under the Blue light source, it shows LED light rate control and light intensity regulation can inhibit the growth of pathogens.